Associations between intima-media thickness of carotid arteries, infectious, immune, and metabolic parameters in healthy people with no risk factors - A. P. Shavrin; B. V. Golovskoy; Ya. B. Khovaeva (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To present the results of the complex assessment of the associations between arterial wall structure and metabolic, infectious, and immune parameters in people free from cardiovascular risk factors (RFs). Material and methods. Among 400 examined healthy participants, aged 18-65 years, 25 did not have any cardiovascular RFs. Vascular ultrasound, with intima-media thickness (IMT) measurement, was performed using ALOKA 5000 device. Laboratory parameters included lipid profile, glucose, plasma C-reactive protein (CRP), pro-inflammatory cytokines, and specific IgG antibodies to CMV, HCV-1, Cl. pneumoniae, H. рylori, and β-streptococcus. Immune status was assessed by innate and acquired immune parameters. Results. A strong association between IMT and viral infectious factors (CMV and HCV-1) was observed. The interaction between infectious factors and arterial wall also involves blood lipids (triglycerides, low- and highdensity lipoprotein cholesterol, total cholesterol) and innate and acquired immune factors. Immune factors regulate vascular wall hemostasis, possibly controlling viral replication and preventing vascular inflammation. This hypothesis is confirmed by low levels of CRP and pro-inflammatory cytokines, as well as by no association between arterial wall thickness and inflammation markers. Conclusion. In healthy subjects without RFs, vascular wall is interacting with viral infectious factors, innate and acquired immune parameters, blood lipids and glucose. All these interactions are balanced and, therefore, do not result in intravascular inflammation.